Martín-Baró, Abib and Holland around with a legitimate citizenship for the Americas - Carrara, Kester (Perspectivas em Análise do Comportamento, 2023)
Writings by J. G. Holland and I. Martín-Baró are examined by J. A. D Abib from the perspective of their implications for the actions of Psychology and, more specifically, of an ethically committed Behavior Analysis, either from the singularities of each theoretical approach in particular, or from of the social environment examined by the two authors. Certain auspicious affinities result from this reflective investigation, keeping the care of language and examples typical of Holland and Martín-Baró’s formulations, which, carefully unveiled by Abib, offer relevant material to provide plausible advances in Behavioral Analysis of Culture and surroundings.